(untitled) (Education in the 21st Century, 2023)
The comparative analysis of higher education management in different countries has become extremely relevant and highly valuable in the world today. These studies address two important issues: i.e. the exchange of cognitive and advanced experience and definitely contributes to the development of Comparative Pedagogy. The article discusses the three most common and applicable models of higher education management in the world: Continental European, Anglo-Saxon, and Humboldtian, presenting the ideas underlying those that are different from each other. Furthermore, the article compares the higher education management of the two EAEU member states - Armenia and Belarus. The similarities and differences, achievements and problems of the management system are presented. In particular, the article presents the reforms implemented in both Armenia and Belarus in the context of the Bologna Process. The comparative analysis concluded that the higher education management system adopted by both Armenia and Belarus fits within the framework of the Continental European model of higher education, with some reference to the Humboldt model. This shows that both Armenia and Belarus have serious reforms in both the quality of education and the democratization of management.